Edukasi Penguatan Sikap Toleransi Kepada Siswa SMAK BASIC Kota Batam - Hudori, Mahfuz; Laudeciska, Leni; Marbun, Destina Veronica; Jevfri, Jevfri; Khelly, Khelly; Yunita, Yunita (Universitas Gajah Putih, Indonesia, 2023)
The population of Batam City is a multicultural society that has a diversity of ethnicities, cultures, and religions. Caring for diversity in Batam City must continue to be done to avoid conflicts such as discrimination and racism. Therefore, the people of Batam City must have good social interactions, where tolerance can be one of the social interactions that must be developed. Among these activities, namely by providing illustrations on strengthening tolerance attitudes and strategic implementation steps to foster tolerance for high school students at BASIC Christian Schools. The objects in this activity are BASIC High School students. Knowledge and understanding of the tolerance attitude of BASIC High School students are measured through the process of observation, interviews, documentation, and filling out questionnaires. Based on the analysis of the data that has been collected, it is concluded that most of the students of BASIC Christian High School already understand the importance of instilling tolerance in schools. This is supported by the policy of the BASIC High School which takes an active role in instilling an attitude of tolerance to its students in the form of providing character education to students about strengthening tolerance in social life for students who have low awareness of tolerance.